Oscillation of fourth-order delay differential equations - Zhang, C.; Li, T.; Saker, S.H. (Нелінійні коливання, 2013)
This article is concerned with oscillation of a certain class of fourth-order delay differential equations. Some new oscillation criteria are presented which include Hille and Nehari type. The results obtained improve some results obtained earlier in [Zhang C., Li T., Sun B., Thandapani E. On the oscillation of higher-order half-linear delay differential equations // Appl. Math. Lett. — 2011. — 24. — P. 1618 – 1621]. Two examples are considered to illustrate the main results. Розглянуто коливання в деякому класi диференцiальних рiвнянь четвертого порядку з загаюванням. Знайдено новi критерiї коливання, якi включають в себе критерiї типу Хiлле та Нехарi. Отриманi результати покращують деякi результати з [Zhang C., Li T., Sun B., Thandapani E. On the oscillation of higher-order half-linear delay differential equations // Appl. Math. Lett. — 2011. — 24. — P. 1618 – 1621]. Розглянуто два приклади, якi iлюструють основнi результати.